Exposure to physical risk factors and health disorders of employees in two dialysis centers of a private institution in 2014. - Albán-Villacís , Jorge (2023)
Introduction: Chronic kidney disease has become a health problem both nationally and globally. The prevalence rate in Ecuador for the year 2022 was 1182.77 ppm and incidence 169.55 ppm. Progressive deterioration of kidney function results in the use of renal replacement therapy (RRT) while waiting for kidney transplantation. In Ecuador, 95% of these patients are not registered on the transplant waiting list. The 5-year survival of patients on RRT is 62%. Objective: Determine the relationship between exposure to physical risk: noise, lighting, temperature, ventilation and humidity; and, the health disorders of the employees of 2 private dialysis centers in Manta and Quito. Materials and methods: A descriptive quantitative research with a cross-sectional design was carried out by applying a survey to staff to determine the presence of symptoms related to the evaluated risks. Data collection was also carried out using lighting measurement devices (Light Meter LUX/FC 840020C), environmental noise (Cirrus 303 Sound Level Meter) and microclimate (humidity, ventilation and temperature). The population under study was made up of 63 medical professionals, 33 belonging to the Manta Dialysis Center and 30 to the Quito Dialysis Center. Results: In relation to noise, in the case of Quito, the measurement carried out gave results within the Comfort ranges, while in Manta, the measurement presented a problem in compliance with the NTP 242 standard, whose upper limit is 65dBA. The personnel who work in the different areas during daylight hours in Quito, in monitoring lighting levels, regarding Reg. 2393, whose minimum level is 100, the average of each area exceeded the minimum limit. In Manta, above the minimum levels established by the SMII (300), the Nursing Station met 100% of the points. There is thermal comfort, according to the Fanger Method, in all the areas evaluated since the result was found within the recommended range. The dialysis equipment contributed to slightly increasing the ambient temperature. When verifying the correspondence between the physical risk factor of humidity, with the responses of problems of skin rashes due to exposure to humidity in the work environment, a Pearson correlation coefficient of 0.680 was obtained; these variables show a relatively strong direct relationship. The physical risk factor for ventilation was related to the answers to the question about suffering from lung diseases caused by working conditions, obtaining a Pearson correlation coefficient of -0.106; does not reflect a correlation between the variables. Conclusions: Exposure to noise and lighting is mild, while in microclimate a medium exposure was found, however, a variation in environmental conditions can alter these exposure levels (increase in machinery, increase in staff and patients, for example). Given this situation, a series of recommendations were developed emphasizing the prevention of these risks in both dialysis centers.